Sifat Sensoris, Kadar Protein dan Zat Besi pada Cookies Daun Kelor - Novitaroh, Ana; Sulistiani, Ria Purnawian; Isworo, Joko Teguh; Syadi, Yunan Kholifatudin (Universitas Muhammadiyah Semarang, 2022)
Cookies are high-energy and sugar snack that is popular in adolescents. Adolescents have a risk of infected anemia. One ingredient food that contains protein and iron which is good forpreventing anemia is Moringa oleifera L leaves. This study aims to determine the effect of addingMoringa leaves on sensory properties, protein, and iron levels in cookies. This research is usingthe True Experiment method with a Completely Randomized Design (CRD). The number ofvariations in the treatment in this study was P0=0 grams of moringa leaves, P1=5 grams, P2=10grams, P3=15 grams. Test for sensory properties using the hedonic test, the protein content testused the Kjedahl method and the iron test used the Spectrophotometric method. The statisticaltest of protein and iron levels used ANOVA. The results showed the best treatment is cookies withthe addition of 10 grams of Moringa leaves (P2). The highest protein content in P3 was 24.609%,and the lowest at P0 18.023% and showed significant differences between treatments. The highestof iron levels in P3 0.015%, and the lowest at P0 0.003% and showed significant differencesbetween treatments. The addition of moringa leaves to cookies affects sensory properties,increases levels of protein and iron.Keywords : Cookies, moringa leaves, protein, iron, sensory properties